Capital adequacy, default risk and macroeconomic shocks in commercial banks in East Asian emerging countries - Janvisloo, Mohammadreza Alizadeh (2015)
Evidence from bank failures due to different types of crises over the past decade has led to banks' capital metrics process to be challenging. One of the most challenging processes is to measure default risk and optimum capital. Market asset value is used to measure default risk and optimum capital to test the health of the banking system. The effect of economic shocks on banks’ default risk is the other issue related to the health of banks, which has been strongly considered in developed countries. In the literature related to these topics, there is a gap in East Asian emerging countries. In this study, the probability of default is primarily estimated based on market information with a Merton’s Option Pricing Model for commercial banks in five emerging countries (Malaysia, Singapore, Korea, Thailand, and Indonesia) for the period of 1995-2013. The estimated default risk varies according to economic conditions and increases noticeably in the disaster time. It also consists of asset qualities such as non-performing loans. The default risk in Indonesia and Korea are always more than the other countries while Singapore has the lowest risk. To meet the second objective, a Global Vector Auto Regressive (GVAR) Model has been used to measure the effects of macroeconomic internal and external shocks on domestic macroeconomic risk factors. The shocks up to 3 standard deviations of variables have been imposed to GVAR Model. Bootstrap median estimation of generalized impulse response functions show that weak exogenous foreign countryspecific variables have significant effects on their domestic corresponding variable. Meanwhile the equity price, real GDP, and real exchange rate are the main transmission channel of shocks’ effects on the domestic macro risk factors. Finally, this study estimates the relationship between the probability of default and macroeconomic risk factors using a dynamic panel data model with a Least Square Dummy Variable Bias Correction (LSDVBC) estimator. The empirical outcome shows that the default risk is explained with different combinations of variables in each country. Meanwhile the equity piece, real exchange rate, real output, and oil price are the most effective variables on the probability of default. The bank size and asset return ratio is the other effectual bank-specific variables on default risk. Based on the impulse response functions, the default risk has been affected by macroeconomic shocks in Malaysian banks more than the other countries. The banks in Indonesian, Korea, Thailand, and Singapore have less been influenced respectively. The banks’ capital conditions is different in these countries and the impact of shocks on the probability of default definitely depends on the initial conditions in terms of capital and market value of their assets as well as their equity volatility, bank size, and asset return ratio. Banks in Singapore have the best condition as the suggested adequate capital ratio is 18.5 percent, which requires a 14 percent increase in capital. In Indonesia, the banks’ capital is not in well status and the capital ratio has to be 24.2 percent due to 51.4 percent increasing in the capital. Korea, Malaysia, and Thailand have relatively been in better and somewhat similar conditions. Hence, they need to improve their adequate capital ratio to 20.6, 20.1, and 21.2 percent while the required capital increase equals 34, 37 and 39.7 percent in average respectively. Therefore following the macroprudential policy and forward-looking approach, it is suggested that the banks' capital to be strengthened before a sudden shock leads to a financial crisis.